2012
DOI: 10.2355/isijinternational.52.823
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Solidification Structure of High Carbon Steel in Continuous Casting Using Cellular Automaton Method

Abstract: A combined cellular automaton-finite difference (CA-FD) model has been developed to simulate solute diffusion controlled solidification in continuous steel casting. Constitutional and curvature undercooling were both solved to determine the equilibrium temperature and growth velocity of the solid/liquid interface. Simulations were firstly performed for both the free dendritic growth from an undercooled melt and the columnar dendritic growth in unidirectional solidification. Finally, competitive dendritic growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…[2,4,5,10,[17][18][19][20][21][22] However, only one previous research reported data on the deflection angle under the influence of M-EMS. In that work, [23] it is indicated that the deflection angle is effected by the solute and temperature gradients induced by fluid flow not by the EM force directly and 60 pct of the imposed electromagnetic force disappears due to the interaction of 3D flow, for example, from the submerged entry nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…[2,4,5,10,[17][18][19][20][21][22] However, only one previous research reported data on the deflection angle under the influence of M-EMS. In that work, [23] it is indicated that the deflection angle is effected by the solute and temperature gradients induced by fluid flow not by the EM force directly and 60 pct of the imposed electromagnetic force disappears due to the interaction of 3D flow, for example, from the submerged entry nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature within a CA cell regarded to be uniform is determined through the bilinear interpolation according to the four temperature nodes around it. [4] The heat flux boundary conditions are applied at the bottom wall of the modeling domain, while the thermal isolation is used for other walls. The value of the heat flux is determined according to mold cooling conditions listed in Table I during SWRH82B steel billet continuous casting process, as expressed in Eq.…”
Section: A Heat Transfer Modelmentioning
confidence: 99%
“…[1][2][3][4] According to the antiparallel relationship between the growth direction of columnar dendrites and the heat flow direction and the upstream growth characteristic, the cooling uniformity and the intensity of electromagnetic stirring (EMS) can be deduced from the growth direction of columnar dendrites in the transverse section of strands. Meanwhile, the dendritic solidification parameters reflecting the cooling intensity, such as primary and secondary dendrite arm spacings, are important to predict the crack susceptibility of steel [5] and the permeability of the mushy zone, [6] which is crucial to accurately investigate the formation and the development of central macrosegregation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations